2020
DOI: 10.3390/nano10071354
|View full text |Cite
|
Sign up to set email alerts
|

Development of Monolithically Grown Coaxial GaInN/GaN Multiple Quantum Shell Nanowires by MOCVD

Abstract: Broadened emission was demonstrated in coaxial GaInN/GaN multiple quantum shell (MQS) nanowires that were monolithically grown by metalorganic chemical vapor deposition. The non-polar GaInN/GaN structures were coaxially grown on n-core nanowires with combinations of three different diameters and pitches. To broaden the emission band in these three nanowire patterns, we varied the triethylgallium (TEG) flow rate and the growth temperature of the quantum barriers and wells, and investigated their effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…GaInN-based nanowires are regarded as one of the promising materials for white-/micro-light-emitting diodes (LEDs) and high-speed optical devices. Nonpolar GaInN/GaN multiple quantum shell (MQS) nanowire structures exhibit low dislocation density inside the n -core, piezoelectric polarization-free active region on m -plane facets, enlarged emission volume on the core–shell structures, and tunable In-incorporation rate with different geometries. These specific features of the coaxial MQS nanowires can address the critical challenges in the conventional c -plane LEDs, especially for high efficacy green and red light emissions. Moreover, the nonpolar nanowire LEDs are of great interest for visible-light communication because they manifest a considerably higher 3 dB modulation speed than conventional c -plane LEDs . However, while the conventional c -plane LEDs have been extensively investigated with high external quantum efficiency (EQE > 80%), , the emission efficiency of coaxial MQS nanowires is still far from commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…GaInN-based nanowires are regarded as one of the promising materials for white-/micro-light-emitting diodes (LEDs) and high-speed optical devices. Nonpolar GaInN/GaN multiple quantum shell (MQS) nanowire structures exhibit low dislocation density inside the n -core, piezoelectric polarization-free active region on m -plane facets, enlarged emission volume on the core–shell structures, and tunable In-incorporation rate with different geometries. These specific features of the coaxial MQS nanowires can address the critical challenges in the conventional c -plane LEDs, especially for high efficacy green and red light emissions. Moreover, the nonpolar nanowire LEDs are of great interest for visible-light communication because they manifest a considerably higher 3 dB modulation speed than conventional c -plane LEDs . However, while the conventional c -plane LEDs have been extensively investigated with high external quantum efficiency (EQE > 80%), , the emission efficiency of coaxial MQS nanowires is still far from commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the emission peak from the apex region of the NWs showed a broad FWHM and strong intensity. The emission region can be flexibly controlled through post-growth etching of the NW apex region, and the geometry of the NW arrays and height of the n-GaN cores enable increased In incorporation in the MQS for the yellow–red emission region. , Here, it has primarily been demonstrated that NW structures with high quality of coaxial MQS and p-GaN shells are promising for NW-based micro-LEDs. A detailed characterization of emission efficiencies in the micro-LED is highly required to further gain insight into the carrier dynamics during operation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Core–shell GaInN/GaN multiple quantum shells (MQSs) on bottom-up grown nanowire (NW) structures have attracted a great amount of attention as a candidate for realization of high-performance white or micro-LEDs. , This is because the MQS NWs manifest high crystalline quality of semipolar r -planes and nonpolar m -planes on the sidewall and a broad tunable InN mole fraction, where the semipolar and nonpolar features enable suppression of the QCSE-induced efficiency droop and blue shift of emission wavelength. Specifically, monolithic growth for different emission colors is also available by varying the pattern pitch and diameter. Moreover, the intrinsic geometry of core–shell MQS-NW arrays can minimize the sidewall surface exposed through dry etching during the chip fabrication process, resulting in suppressed sidewall damage and detrimental surface defects. This is because NWs located outside of the mesa area are allowed to be selectively removed by ultrasonic cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce such TDs, methods for increasing the crystal quality of active layer on the c-plane can be adopted, for example, the growth method of the active layer proposed previously. [25,42,43] Another method is to form the tip of the NWs with only inclined faceted {10-1n} plane, because the active layer on the {10-1n} plane of the NWs has a slower growth rate and is thinner than those on the c-plane of NWs, [41,42] and thus, defects due to the lattice mismatch and growth error are less likely to form. However, in the NW-MQS structure, it is difficult to selectively only the active layer on the c-plane because the active layer is simultaneously formed on all crystal planes of the NWs.…”
Section: Discussion On the Mechanism Of Defect Formationmentioning
confidence: 99%